2011
DOI: 10.1016/j.ajog.2011.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and antiinflammatory cytokines in threatened miscarriages

Abstract: OBJECTIVE:The purpose of this study was to evaluate circulating and intracellular levels of Th1 and Th2 cytokines in women with threatened miscarriage (TM) and subsequent outcome.STUDY DESIGN: Plasma levels of tumor necrosis factor (TNF)-receptors 1 and 2, TNF␣, interferon gamma (IFN␥), and interleukins (IL) -6 and -10 were measured by flow cytometric bead assays in 80 women with TM: 53 women with normal outcome and 27 women who miscarried. Fluorescent antibody labeling was also performed on whole blood in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 73 publications
1
35
0
2
Order By: Relevance
“…Recently, studies have shown that altered levels of these receptors in the circulation, in combination with other cytokines and/ or hormones, may play a role in predicting miscarriage in patients presenting with threatened miscarriage. 206 Future clinical trials are needed to study the possible benefit of anti-TNF treatment in pregnancy complications.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have shown that altered levels of these receptors in the circulation, in combination with other cytokines and/ or hormones, may play a role in predicting miscarriage in patients presenting with threatened miscarriage. 206 Future clinical trials are needed to study the possible benefit of anti-TNF treatment in pregnancy complications.…”
Section: Resultsmentioning
confidence: 99%
“…Different investigations indicated the roles of increased Th1/Th17 and decreased Th2/Treg patterns and their cytokines in recurrent miscarriages and preeclampsia [9,15,17,18]. For example, Wang et al [19,20] reported an increased number of Th17 cells in placental tissues and a high level of IL-17 cytokine in peripheral blood of women with recurrent miscarriage.…”
Section: Inflammation and Pregnancy Complicationsmentioning
confidence: 99%
“…Calleja-Agius et al [17] found increased levels of TNF-α/IL-10 and IFNγ/IL-10 ratios in pregnant women who had a high risk of miscarriage. Inflammatory cytokines TNF-α and IL-6 also involve in the pathphysiology of hypertension during preeclampsia [21].…”
Section: Inflammation and Pregnancy Complicationsmentioning
confidence: 99%
“…Abnormal maternal immune response has been proposed to be one of the mechanisms underlying RM. 3 Multiple factors, such as the cytokine environment and costimulatory molecules present during activation of the naive T-helper cell, determine the development of either Th1-or Th2-helper phenotype. 2 An increased Th1 type of immune response was observed in women undergoing RPL or threatened miscarriages.…”
Section: Introductionmentioning
confidence: 99%